2005
DOI: 10.1086/429358
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity and HiColumn Density Properties of Damped Lyα Systems

Abstract: On the basis of the disk galaxy formation theory within the framework of the standard ÃCDM hierarchical picture ( Mo, Mao, & White), we selected modeled damped Ly systems ( DLAs), according to their observational criterion N H i k 10 20:3 cm À2 by Monte Carlo simulation using random inclinations to examine their observed properties. By best-fitting the predicted metallicity distribution to the observed ones, we get an effective yield of about 0:25 Z for DLAs, which is comparable to those for the SMC and LMC. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…Although a difference can be seen in the range −1.6 < [X/H] < −1, partly due to the bias towards large N(H i), no systematic bias is observed for the UVES sample, apart from any also affecting the Keck sample, as shown by the cumulative distributions (inset). We note that the observed distributions are similar in shape to the distribution derived using simulations by Hou et al (2005, their Fig. 3).…”
Section: Overall Populationsupporting
confidence: 80%
“…Although a difference can be seen in the range −1.6 < [X/H] < −1, partly due to the bias towards large N(H i), no systematic bias is observed for the UVES sample, apart from any also affecting the Keck sample, as shown by the cumulative distributions (inset). We note that the observed distributions are similar in shape to the distribution derived using simulations by Hou et al (2005, their Fig. 3).…”
Section: Overall Populationsupporting
confidence: 80%
“…Potentially, these could be caused by flat-field errors which become larger at the edges in the PMAS data cubes, but they do satisfy the criteria for being good DLA candidates. The average impact parameter of ∼20 kpc derived for the candidates is larger than expected by numerical simulations, favouring impact parameters of 3 kpc for typical DLA galaxies, with only few DLA galaxies having b > 10 kpc at both high and low redshifts (Okoshi & Nagashima 2005;Hou et al 2005).…”
Section: Impact Parametersmentioning
confidence: 56%
“…This implies that a typical DLA host galaxy in our model has its SFR 100 times smaller than a typical LBG. Because the number density of DLA host galaxies is about 0.26 (Hou et al 2005) which is about 100 times larger than the observed comoving number density of LBGs, our predictions of cosmic SFR density contributed by DLAs is similar to that of LBGs at z ∼ 3.…”
Section: Cosmic Star Formation Rate Density From Dlas Host Galaxiesmentioning
confidence: 59%
“…Details can be found in Mo et al (1998) and Hou et al (2005). We use Monte Carlo simulation to generate the model DLAs by applying a random sight line passing through the disk.…”
Section: The Modelmentioning
confidence: 99%